2006
DOI: 10.1002/uog.2796
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pulmonary venous Doppler parameters in fetal cardiac defects

Abstract: K E Y W O R D S:abnormal pulmonary venous drainage; congenital heart defects; fetal pulmonary veins; pulmonary venous obstruction; venous Doppler ABSTRACT Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 46 publications
(64 reference statements)
5
14
1
2
Order By: Relevance
“…This mirrors the flow patterns described in late pregnancy by previous studies [7,10,11]. A pulmonary vein A-wave reversal was only described in 0.55 % of normal fetuses.…”
Section: Detection Of Fetal Pulmonary Venous Flow Waveforms During Easupporting
confidence: 88%
See 3 more Smart Citations
“…This mirrors the flow patterns described in late pregnancy by previous studies [7,10,11]. A pulmonary vein A-wave reversal was only described in 0.55 % of normal fetuses.…”
Section: Detection Of Fetal Pulmonary Venous Flow Waveforms During Easupporting
confidence: 88%
“…The heart defect was described as a right ventricle hypoplasia with tricuspid atresia, VSD and patent foramen ovale. This finding is supported by the study by Lenz et al [11] where all right side anomalies presented with normal end-diastolic pulmonary venous flow. We propose that alteration in pulmonary venous flow might mainly reflect left heart anomalies.…”
Section: End-diastolic (A-wave) Pulmonary Venous Flow Reversal and Cosupporting
confidence: 76%
See 2 more Smart Citations
“…Recent advances in high-resolution ultrasound (Bonnet et al, 1999;Brackley et al, 2000;Cohen, 2001;Denkhaus et al, 1979;Hamar et al, 2006;Hecher et al, 1995;Tworetzky et al, 2001) and fetal cardiac MRI (Coakley, 2001;Fogel, 2006;Fogel et al, 2005;Hubbard et al, 1999;Liu et al, 2001) have demonstrated that aortic arch hemodynamics (Lenz et al, 2006) and great vessel anatomy (Axt-Fliedner et al, 2006;Hubbard et al, 1999) correlate with the prognosis of patients with complex CHD, However, fetal cardiac imaging modalities have practical limitations. Fetal echocardiography is often not a true 4D modality, has limited field-of-view, and is constrained by acoustic maternal and fetal windows.…”
Section: Discussionmentioning
confidence: 99%